Karta ateńska jako próba określenia zasad nowoczesnej urbanistyki i jej wpływ na kształt przestrzeni miast polskich XX w. - Rogowska, Małgorzata (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The article describes the one of new urban conceptions of the beginning of the 20th Century and influence on the Polish urban space. Cities are constantly changing, the dwelling needs are increasing in connection with arriving of more and more new inhabitants to the urban areas. The vision of the 20th century town-planners and be the background to begin new analysis and searching the most important issues that designate an ideal city. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1087, s. 124-133